The Comprehensive Management of Diabetes Mellitus: A Literature Review - Abidzah, Rendy Zayyan; Wardhani, Fitria Kusuma (Faculty of Medical - UPN Veteran Jawa Timur, 2024)
ABSTRACTBackground: The number of people with diabetes mellitus (DM) increased from 108 million in 1980 to 422 million in 2014. Prevalence is increasing faster in low- and middle-income countries than in high-income countries. The rapid increase in the number of people with diabetes is a global crisis that places a huge burden on public health systems.1Methods. Literature searching was conducted using databases such as PubMed, Google Scholar, and Web of Science using Search terms included